The Factors of Social Strengths and Weakness Faced to A Construction Process of Social Support of Tuberculosis’s Sufferer - Andi Agustang; Abd Hady (JED (Jurnal Etika Demokrasi), 2022)
This study examines any determinant factor of social strengths and weakness that face to a construction process of social support for patients of tuberculosis sufferers, with qualitative methods and case study designs, phenomenology, analytic, comparative, and explorative. The result is that social power factors to face them include:(1) local cultural wisdom values, (2) social norms owned family and community, (3) potential types of social support, (4) potential social relationships in family and community behavior, (5) potential lifestyle changes, (6) positive perceptions of families and communities, (7) health or medical information and socialization, (8) positive social impacts of TB disease, (9) DOTS or TOSS policies or programs. While the social weakness factors are (1) the potential for shifting and neglecting the values of local cultural wisdom, (2) the potential for neglecting the socio-cultural norms of family and society, (3) the potential for neglecting social support, (4) the potential for estrangement in social relations (kinship, brotherhood, friendship) in family and community social behavior, (5) status quo lifestyle behavior, (6) potential negative perceptions of TB SPP, family, and society, (7) potential for stereotypes, stigma-labeling, (8) potential social discrimination and conflict, (9) the potential for social oppression of sufferers, (10) information gaps and health/medical socialization, (11) the negative impact of TB disease, (12) inequality in the implementation of DOTS/TOSS. Penelitian ini mengkaji model konstruksi dukungan sosial penderita penyakit tuberculosis, dengan metode kualitatif dan desain case study, fenomenologi, analitik, comparative, eksploratif. Hasilnya bahwa faktor kekuatan sosial dalam konstruksi dukungan sosial penderita penyakit tuberculosis meliputi (1) nilai-nilai kearifan budaya lokal, (2) norma-norma sosial keluarga dan masyarakat, (3) potensi jenis dukungan sosial, (4) potensi hubungan sosial perilaku keluarga dan masyarakat, (5) potensi perubahan gaya hidup, (6) persepsi positif keluarga dan masyarakat, (7) informasi dan sosialisasi kesehatan/medis, (8) dampak sosial penyakit Tb secara positif, (9) kebijakan/ program DOTS atau TOSS. Sedangkan factor kelemahan sosial adalah (1) potensi pergeseran dan pengabaian nilai-nilai kearifan budaya lokal, (2) potensi pengabaian norma-norma sosial budaya keluarga dan masyarakat, (3) potensi pengabaian dukungan sosial, (4) potensi kerenggangan hubungan sosial (kekeluargaan/ kekerabatan, persaudaraan, persahabatan) dalam perilaku sosial keluarga dan masyarakat, (5) perilaku gaya hidup statusquo, (6) potensi persepsi negatif SPP Tb, keluarga, dan masyarakat, (7) potensi stereotype, stigma-labelling, (8) potensi diskriminasi sosial dan konflik, (9) potensi opresi sosial subyek penderita, (10) kesenjangan informasi dan sosialisasi kesehatan/medis, (11) dampak negatif penyakit Tb, (12) ketimpangan implementasi kebijakan/ program DOTS/ TOSS.